TECHNOLOGY FOR ADMINISTERING OF THE ACCESS TO INFORMATION RESOURCES IN MANAGEMENT SYSTEM ON THE AVIATION ENTERPRISE - Andrey V. Degtyarev; Vladimir A. Vdovin; Serge E. Pyatovsky (Статистика и экономика)
The task of administering software-information complex occurs duringthe development of application systems for managing business-processes and is connected with the organization of access forusers to information resources in conditions of multi-user information systems for management. For solution of this problem proposed theapproach, which is based on a hierarchical system of access rightsto information resources on the levels: tool, object and procedural.Keywords: software-information complex, information resources,administering, permissions, separation of powers, access model.